Bilingualism of Two Indonesian Siblings Living in Australia - Dwi Rahayu (Universitas Syiah Kuala, 2016)
Attitude is one of the most prominent issues in bilingualism. It becomes crucial and interesting because it is related to how speakers preserve their language to avoid language attrition and to maintain their established language competence. This study investigates the attitudes of two Indonesian siblings, a 19-year old and a 24-year old, who migrated to Australia with their parents in 2002. This study looks into their attitudes towards their Indonesian L1 after living for 11 years in Australia. An interview was conducted along with a guided questionnaire with both participants. The results revealed that their attitudes toward their Indonesian L1 are different regardless of having had the same treatments from their parents. The younger sibling seems to be more reluctant to use his Indonesian L1 and now, he has difficulties in speaking in Indonesian. Accordingly, the possibility of his partial loss of his L1 was indicated. The results further show that their different attitudes are one of the factors that foster the language loss suffered by the younger participant, especially the loss of vocabulary knowledge. The study also found some demographic factors such as the age of onset and the level of education when he started studying at an Australian school that may have influenced the difficulties that the younger participant has with production of his L1.